The Degree of Kindergartens' Principals' Application of Business Processes Re-engineering Principles and its Relation to the Degree of Their Application of Administrative Creativity According to Teachers A Field Study at Kindergartens in Lattakia - Ali, Naifah; Ahmad, Mutieah; Abbas, Sawsan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims at determining the degree of application of kindergarten principals in lattkia city of the principles of Business Processes Re-engineering and the elements of administrative creativity from the point of teachers view, and studying whether there is a statistic relationship between the degree of application of kindergarten principals in lattkia city of the principles of Business Processes Re-engineering and the elements of administrative creativity from the point of teachers view. In order to achieve the goals of this research, a questionnaire was built and distributed over (180) kindergarten teachers through Lattkia city. There were received (179) questionnaires bach of the total number distributed. According to the received questionnaires and a depending on suitable statistics methods. The following results were concluded: 1- The degree of application of kindergarten principals in lattkia city of the principles of Business Processes Re-engineering is high from the point of teachers view. 2- The degree of application of kindergarten principals in lattkia city of the elements of administrative creativity is high from the point of teachers view. 3- - There is a relationship strong positive of a statistic indication of (a=0.05) between application of kindergarten principals of the principles of Business Processes Re-engineering and the degree of application of the elements of administrative creativity. The research recommened: - That the Directorate of Education makes training workshops for kindergartens' principles, and that is important in order to guide them to adopt modern management entrances. - Encouraging kindergartens' principles to be creative in their work through what the Directorate of Education offers like facilities, incentives, support, and encouragement to creative kindergartens.